Decision Making: Intra-arterial Therapies for Cholangiocarcinoma—TACE and TARE - Currie, Brian M. (Semin Intervent Radiol, 2017)
The incidence of intrahepatic cholangiocarcinoma (ICC) has been increasing in recent years and now represents the second most common primary hepatic cancer in the United States. The prognosis is dismal without surgical resection. In patients ineligible to receive curative treatments, locoregional therapies represent a diverse array of techniques that can stabilize or reverse tumor progression to improve overall survival and reduce tumor-related symptoms. Transarterial chemoembolization (TACE) and transarterial radioembolization (TARE) have been demonstrated to be efficacious methods for this patient population. Deciding between these two options is challenging. This article reviews the differences in patient selection, preprocedural evaluation, financial considerations and availability, quality of life, and rates of complications and overall survival.